Frozen Bodies and Future Imaginaries: Assisted Dying, Cryonics, and a Good Death - Jeremy Cohen (Religions, 2020)
In October of 2018, Norman Hardy became the first individual to be cryopreserved after successful recourse to California’s then recently passed End of Life Options Act. This was a right not afforded to Thomas Donaldson, who in 1993 was legally denied the ability to end his own life before a tumor irreversibly destroyed his brain tissue. The cases of Norman Hardy and Thomas Donaldson reflect ethical and moral issues common to the practice of assisted dying, but unique to cryonics. In this essay, I explore the intersections between ideologies of immortality and assisted dying among two social movements with seemingly opposing epistemologies: cryonicists and medical aid in dying (MAiD) advocates. How is MAiD understood among cryonicists, and how has it been deployed by cryonicists in the United States? What are the historical and cultural circumstances that have made access to euthanasia a moral necessity for proponents of cryonics and MAiD? In this comparative essay, I examine the similarities between the biotechnological and future imaginaries of cryonics and MAiD. I aim to show that proponents of both practices are in search of a good death, and how both conceptualize dying as an ethical good. Cryonics members and terminal patients constitute unique biosocial worlds, which can intersect in unconventional ways. As temporalizing practices, both cryonics and MAiD reflect a will to master the time and manner of death.